Study guide essentials of anatomy & physiology - Smith, Robert R. (Prentice Hall, 1997)
Designed to help students master the topics and concepts covered in the textbook, the study guide includes a variety of review questions, including labeling, concept mapping, and crossword puzzles, that promote an understanding of body systems. It is keyed to each chapter's learning objectives and parallels the three-level learning system in the textbook